Analysis of fourth-grade fluid model over a stretchable surface with Riga plate subject to permeable medium. Issue 3 (1st June 2022) - Hua, Bian; Shah, Faisal; Khan, M Ijaz; El-Zahar, Essam Roshdy; Farooq, Shahid; Khan, Sami Ullah; Guedri, Kamel; Wu, Wen-jing
Abstract: The current investigation is concerned with the rheological impact of fourth-grade confined by Riga surface. The flow behaviour is analysed over a Riga plate in the presence of stagnation point and porous medium. The relevant similarity variables and corresponding boundary conditions are adopted to model the current problem. The highly non-linear coupled differential system is via optimal homotopy scheme. The outcomes of relevant dimensionless parameters on the velocity profile have been visualized with physical exploration. It is observed from the obtained outcomes that the fluid velocity declines against rising estimations of modified magnetic variable and inverse Darcy number. The increasing velocity change is noted for boosting values of third-grade fluid parameter. Moreover, the velocity pattern for fourth-grade material is comparatively higher than viscous, second-grade, and third-grade materials. The comparative analysis against obtained simulations is also listed. Graphical Abstract: